Dependability Evaluation and Supervision in Thermal Power Plants - Marwa Ben Hamouda; Mohamed Najeh Lakhoua; Lilia El Amraoui (Institute of Advanced Engineering and Science, 2015)
In order to improve the productivity and the consistency of its maintenance strategies, the industrial world is based on different techniques and tools developed to ensure safe operation and the supervision of production systems. In fact, dependability evaluation is crucial to controlling the risks associated with system failure, and for this reason, it is one of the fundamental steps in automated system design. In this paper, we present firstly the basic concepts for the study of dependability as well as functional systems analysis. Thus, we present the method SADT (Structured Analysis Design technique). Given the ineffectiveness of methods that are currently exploited are not appropriate because the level of complexity of such industrial systems, we propose in the first the Safe-SADT method which allows the explicit formalization of functional interaction, the identification of the characteristic values affecting complex system dependability, the quantification of RAMS parameters (Reliability, Availability, Maintainability, and Safety) for the system’s operational architecture. Secondly, a methodology for designing supervisory production systems has been presented and has been applied on an example of a SCADA (supervisory control and data acquisition) system of a thermal power plant. Finally, a model of operating safety and supervision of a production system is proposed.